Implementation of a built-in self-test for nuclear power plant FPGA-based safety-critical control systems. (January 2022) - Lin, Zequn; Wang, Lingzhi; Cai, Yuanfeng; Wang, Fanyu; Wu, Yichun
Highlights: The built-in self-test method for nuclear power plants safety-critical FPGA-based system is proposed. The partition strategy of built-in self-test simplifies the test structure. The built-in self-test method improves the self-diagnosis coverage and reduces the test effort. An FPGA-Based Reactor Trip System built-in self-test logic example is provided. Abstract: Field-programmable gate arrays (FPGAs) are being widely used in the instrumentation and control (I&C) systems of nuclear power plants (NPPs). However, FPGAs have the possibility of failure, resulting in the reliability not being fully guaranteed; therefore, some methods are required to evaluate and verify their reliability. The built-in self-test (BIST) method is a technology that implants relevant functional circuits into another circuit during design to provide self-test functions. It has many advantages over external test devices. For this study, the FPGA-based reactor protection subsystem of the CPR1000 NPP was selected as the test object. This paper presents the principle of system partition, the main objective of which is to reduce the test time and provide convenience for subsequent modifications; then, we use the BIST method and build the BIST architecture to test each input signal channel as a black box. For several common failures, 100% diagnostic coverage can be obtained, which improves the reliability of a protection system. BIST can be used as a supplement to external tests; it can reduce the test time, reduce testing costs, and solve many problems that cannot be solved using external tests, such as the lack of interfaces. The research results provide theoretical and technical references for the application and review of FPGA-based applications in NPP safety–critical systems.